Open educational practices and resources based on social software, UTPL experience - Piedra Pullaguari, N. (2009)
Open Educational Practices and Resources are a direct response to privatization of knowledge; they promote their exchange across the world with the aim of increasing human intellectual capacity. In this document we will discuss the Open Educational Practices and Resources Movement and the notion that knowledge is a public good where technology in general, and specifically Web 2.0, provide an extraordinary opportunity for people to acquire key competences in a knowledge society while they share, use, and re-use digital contents. We will describe the key function of tools and services based on Social Software in the Web 2.0 environment in the OERs production, based on experiences gained at the Universidad Técnica Particular de Loja (Ecuador). Moreover, we describe the commitment of the University to the promotion of open educational practices and resources and their impact on society and knowledge economy. This is accomplished through the use of Social Software as a potential key to producing changes in the actual production model, moving from a hierarchical transfer of knowledge from the teacher to a new range of open and collaborative educational practices centered on the student. Copyright 2009 ACM.